Effect of match load on perceived wellness in highly trained female football players - Ivan Baptista; Andreas Alexandersen; Andreas K. Winther; Dag Johansen; Svein Arne Pettersen (PLoS ONE, 2025)
Background Exposure to match loads significantly affects physiological and psychological indicators and, consequently, players’ wellness. However, this information is still scarce in women’s football. Therefore, the aims of this study were twofold: a) to compare the wellness variation from matchday (MD) to two days post-match (MD+2); b) and to analyse the correlations between the players’ external load on MD and the self-reported wellness on the day after the match (MD+1) and MD+2. Methods This retrospective cohort study included data from 22 weeks and 33 official matches from 18 professional and semi-professional female football players competing in the Norwegian top-tier. Signals for total distance, high-speed running distance (>16 km/h-1), sprint distance (>20 km/h-1), acceleration distance, and number of sprints were collected using a Global Positioning System. Sleep duration and four wellness subsets were included in this study: sleep quality, delayed onset muscular soreness, fatigue and stress levels. Individual models were run using the respective wellness variable as the dependent variable, with matchday as a predictor. Data was modelled using cumulative link regression models. The model allowed random slopes for subjects to account for repeated measurements. Correlation analysis was computed using Spearman’s rank correlations. Results Our results from the cumulative link regression model suggest that fatigue increased on MD+1 (Estimate: 1.30; SE=0.16; p<0.001) and remained elevated on MD+2 (Estimate: 0.75; SE=0.15; p<0.001), when compared to MD. Sleep quality decreased on MD+1 (Estimate: -0.72; SE=0.14; p<0.001). Sleep duration decreased on MD+1 (Estimate: -0.70; SE=0.13; p<0.001) and on MD+2 (Estimate: -0.61; SE=0.13; p<0.001). Moderate correlations were observed on MD+2 between sleep duration and acceleration distance (0.32, p<0.001) and high-speed running distance (0.30, p<0.001). Conclusions Competitive matches are associated with a disruption in the stability of the players’ sleep patterns and wellness. The results also suggest that univariate external load measures may not be strong enough to predict the players’ wellness status variation in the days following matches.